Implementasi Akuntabilitas Dalam Konsep Metafora Amanah di Lembaga Bisnis Syariah (Studi Kasus : Swalayan Pamella Yogyakarta) - Rahmah Yulisa Kalbarini; Noven Suprayogi (Universitas Airlangga, 2014)
This study is aimed to find out accountability within Trustful metaphor concept and know the process also type of accountability in islamic business organization case study at Pamella Supermarket.The methods of this study is qualitative approach using research study. The analyze technique is domain and taxonomy. Data is collected by interview, passive participant observation, and secondary data. The informants of this research are an assistant manager, a marketing officer, an employee and costumers of the Pamella Swalayan in Yogyakarta.The results obtained, that the implementation of accountability with trustful metaphor concept in Pamella Supermarket based on pamella owner’s concept on accountability that the purpose of life is rahmatan lil alamin that is each muslim can give a benefit to of the muslims. The realization of that concept is there will be a separation of responsibility : business fund from social fund which is managed by Pamella. From the supermarket sight, the business fund is under the responsibility of the owner and to Allah SWT. While the social fund is under the responsibility of the society by holding some social humanity program, which are reported to the society as well as to the existing interrelated departments in Yogyakarta. REFERENCESAbdurrahman, Nana Herdiana. 2013. Manajemen Bisnis Syariah dan Kewirausahaan. Bandung: CV. Pustaka Setia.Afifuddin dan Beni Ahmad Saebani. 2009. Metodologi Penelitian Kualitatif. Jakarta: Pustaka Setia.Almath, muhammad faiz. 1991. 1100 Hadits Terpilih. Jakarta: Gema Insani.Basri, Hasan dan Siti Nabiha Abdul Khalid. April 2012. Examining Accounting and Accountability Issues in Religious. Aceh International Journal of Social Sciences. Volume 1, No. 1: 24-31.Departemen Agama. 2002. Mushaf AlQur’an Terjemah. Jakarta: Pena Pundi Aksara.Harahap, Sofyan syafri. 2001. Menuju Perumusan Teori Akuntansi Islam. Jakarta: PT. Pustaka Quantum.Harahap, Sofyan syafri. 2004. Akuntansi Islam. Jakarta: PT. Bumi Aksara.Harahap, Sofyan Syafri. 2008. Kerangka Teori & Tujuan Akuntansi Syari’ah. Jakarta: Pustaka Quantum.Haryadi, Bambang. 2010. Political Economy of Shariah Accounting (Membangun Teori Ekonomi Politik Akuntansi Syari’ah). Malang: Pascasarjana Universitas Brawijaya.Kholmi, masiyah. Juni 2012. Akuntabilitas dan Pembentukan Perilaku Amanah dalam Masyarakat Islam. Volume 15, No. 1: 63-72.Kiswanto dan Hasan Mukhibad. September 2011. Analisis Budaya Islam Dan Akuntabilitas. Jurnal Dinamika Akuntansi. Volume 3, No. 2: 77-89. Muhammad. 2002. Pengantar Akuntansi Syari’ah. Jakarta: Salemba Empat.Mulawarman, Aji dedi.2009. Akuntansi Syariah (Teori, konsep, dan laporan keuangan). Jakarta: E-Publishing Company.Noor, Ali Fikri.2014. Serial Akhlak Muslim: Amanah. Jakarta: e-book.Permatasari, Nurhidayah Chairany dan Nurul Hasanah Uswati Dewi. July 2011. Pandangan Pemilik Badan Usaha Islam Terhadap Akuntabilitas Dan Moralitas. The Indonesian Accounting Review. Volume 1, No. 2: 135 – 144. Priansa Donni Juni dan Buchari Alma. 2009. Manajemen Bisnis Syari’ah. Bandung: Alfabeta.Shihab,M. Quraisy. 2009. Tafsir Al-Mishbah Pesan, Kesan, dan Keserasian AlQur’an. Jakarta: Lentera Hati.Soetedjo, Soegeng. 2009. Pembahasan Pokok-pokok Pikiran Teori Akuntansi Vernon Kam. Surabaya: Airlangga University Press. Sugiyono. 2012. Memahami Penelitian Kualitatif. Bandung.Alfabeta. Tampubolon, Manahatan P. 2008. Perilaku Keorganisasian (Organizing Behavior) Perspektif Organisasi Bisnis. Bogor: Penerbit Ghalia Indonesia.Triyuwono, Iwan dan Moh Mashudi. 2001. Akuntansi Syari’ah (Memformulasikan Konsep Laba dalam Konteks Metafora Zakat). Jakarta: Salemba Empat.Triyuwono, Iwan. 2000. Organisasi dan Akuntansi Syari’ah. Yogyakarta: LkiS.Triyuwono, Iwan. 2006. Akuntansi Syari’ah (Perspektif, Metodologi, dan Teori) edisi II. Jakarta: PT. Rajagrafindo Persada.(www.suratpembaca.detik.com tanggal 6 november 2013 diakses pada tanggal 6 Juli 2014).(www.pamellagroup.blogspot.com) Diakses tanggal 4 februari 2013 pukul 20.12.